Effect Of Cooking Duration Using Merandang Technique On Organoleptic Quality Of Beef Rendang - Victor Kurniawan Yuwono; Fabiola Leoparjo; Devina Irtanto; Mazaya Azka Ridhauddhin; Raihan Nur Shabrina; Mario Alfrenzo Hartojo (Universitas Negeri Padang, 2026)
Rendang is a traditional Minangkabau dish prepared using the merandang technique, which involves slow-cooking meat with coconut milk and spices over a long period to produce a dry dish with complex sensory characteristics. In the modern era, the lengthy merandang process raises efficiency concerns and may affect sensory quality. This study aimed to analyze the effect of cooking duration on the organoleptic quality of beef rendang and to determine the most preferred cooking duration. This research used a quantitative experimental method with an organoleptic acceptance test involving three cooking duration treatments: 4 hours, 5 hours, and 6 hours. The test was conducted with 50 untrained panelists using several sensory parameters, including color, aroma, initial texture, chewing texture, taste preference, seasoning intensity, and overall acceptance. The data were analyzed using ANOVA with SPSS, followed by a post-hoc test to identify differences among treatments. The results showed that cooking duration significantly affected several organoleptic parameters, namely color, aroma, initial texture, chewing texture, seasoning intensity, and overall acceptance, as indicated by different letter notations at a significance level of p < 0.05. The 5-hour treatment code 291 obtained the highest scores for initial texture 5.26, chewing texture 5.46, and overall acceptance 5.44. Therefore, the 5-hour cooking duration can be recommended as the optimal duration because it produced the highest overall acceptance compared with the 4-hour and 6-hour treatments.